PREVALENCE, RISK FACTORS AND MANAGEMENT OF PARALYTIC ILEUS AMONG PATIENTS IN SAUDI ARABIA: SYSTEMATIC REVIEW - ALGHAMDI, AYMAN GHURMULLAH SALEH; ALDOSARI, OMAR MUHAMMED F; ALWADAI, SAAD ALI MOSLEH; ALYAHYA, SAEED ALI SAEED; ALASMREE, ABDULRAHMAN DULAYM A.; ALQAHTANI, MOHAMMED SAEED MOHAMMED; ALFARWAN, SAAD ALI; ALMASSAUD, HISHAM AHMED ALI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Introduction: When the bowel's motor activity is compromised, a condition known as paralytic ileus occurs. This condition is typically unrelated to a mechanical issue. Despite the possibility of self-limitation, the condition is dangerous and, if left untreated for a long period of time, will cause mortality in a manner similar to acute mechanical obstruction. Knowing the most likely etiology and the likelihood that the condition can be managed without surgery are key factors in paralytic ileus management. Methodology: PubMed, Web of Science, Science Direct, EBSCO, and Cochrane library were searched. Study articles were screened by title and abstract using Rayyan QCRI then a full-text assessment was implemented. Results: A total of 5 studies with both sex and random age patients diagnosed with paralytic ileus were included in this review; more than half were males. Conclusion: There is a lack of literature on paralytic ileus prevalence and risk factors among saudi patients. One of the obstacles to improving the fight against POI is the lack of consensus on its definition, making the literature non comparable. While the majority of measures aim more at the prevention of POI than its treatment, it is logical to think that, just as with gum chewing, patient “prehabilitation” could improve the effectiveness of prevention.